The expanding role of cap-adjacent modifications in animals - Bellows, Eleanor; Fray, Rupert G.; Knight, Helen M.; Archer, Nathan (Frontiers in RNA Research, 2024)
Eukaryotic mRNA cap structures directly influence mRNA stability, translation, and immune recognition. While the significance of the mRNA cap itself has been well-established, recent research has revealed the intricate modifications to the nucleotides immediately adjacent to the cap.These include 2'-O-methylation (Cap1, Cap2) and N6-methyladenosine (m6Am), which recent work suggests may be dynamically regulated, interdependent, and vital for gene-regulation. This perspective explores this expanding role of cap-adjacent modifications.Cap1 is found on metazoan mRNA, viruses which infect metazoans, and the COVID-19 mRNA vaccines. We combined basic local alignment and 2D-TLC to track cap-adjacent modifying proteins and the modifications themselves to track their prevalence throughout eukaryotes. We confirm that Cap1 is broadly metazoan specific, but surprisingly also in a brown algae.Additionally, we find genomic presence of the eraser, FTO more predictive of the occurrence of m6Am than the m6Am-writer, PCIF1. We then outline future directions to understand and exploit these enigmatic modifications.